1954
DOI: 10.1063/1.1721649
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Internal Friction and Elasticity Effects in Vitreous Silica

Abstract: Near 35°K the internal friction of vitreous silica reaches a peak value which increases with frequency. The temperature curves of the torsion and Young's moduli are concave upward with minima near 65°K and are independent of frequency. These effects are reversible with temperature. Their cause cannot be the usual type of relaxation process or anything involving diffusion or large amounts of shear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

1975
1975
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(33 citation statements)
references
References 6 publications
2
31
0
Order By: Relevance
“…Many studies (for example, Refs. [35,38]) found that the Q-value of the bulk SiO 2 has a local minimum (about 10 3 ) of around 30 K.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies (for example, Refs. [35,38]) found that the Q-value of the bulk SiO 2 has a local minimum (about 10 3 ) of around 30 K.…”
Section: Discussionmentioning
confidence: 99%
“…Future, more sensitive detectors such as upgrades to Advanced LIGO [2] and the low frequency detector within the Einstein Telescope (ET) [3,4] may be operated at cryogenic temperatures to reduce thermal noise. The presently used test-mass material fused silica becomes unsuitable at low temperatures due to high mechanical loss and thus high thermal displacement noise [5]. A promising replacement material with low mechanical loss at cryogenic temperatures is crystalline silicon (cSi) [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Data from Vonnegut and Glathart [1946] Data from Fine et al [1954], McSkimin [1953], and Spinner and Cleek [1960] ..............98 Data from Fine et al [1954] and McSkimin [1953] Data from Mamedov et al [1985;1987], Zeller andPohl [1971], and Flubacher et al [1959] Touloukian et al [1977], Gibbons [1959;citations therein], and White [1973] al. [1977].…”
mentioning
confidence: 99%